High‐level iron mitigates fusaricidin‐induced membrane damage and reduces membrane fluidity leading to enhanced drug resistance in Bacillus subtilis. (15th October 2015) - Yu, Wen‐Bang; Ye, Bang‐Ce
Abstract : Fusaricidins are a class of cyclic lipopeptide antibiotics that have strong antifungal activities against plant pathogenic fungi and excellent bactericidal activities against Gram‐positive bacteria. The mechanism through which fusaricidin exerts its action is not yet entirely clear. To investigate the mode of action of fusaricidin, we determined the physiological and transcriptional responses of Bacillus subtilis to fusaricidin treatment by using a systems‐level approach. Our data show that fusaricidin rapidly induced the expression of σ W regulon and caused membrane damage in B. subtilis . We further demonstrated that ferric ions play multiple roles in the action of fusaricidin on B. subtilis . Iron deprivation blocked the formation of hydroxyl radical in the cells and significantly inhibited the bactericidal activity of fusaricidin. Conversely, high levels of iron (>2 mM) repressed the expression of BkdR regulon, resulting in a smaller cellular pool of branched‐chain precursors for iso‐ and anteiso‐branched fatty acids, which in turn led to a decrease in the proportion of branched‐chain fatty acids in the membrane of B. subtilis . This change in membrane composition reduced its bilayer fluidity and increased its resistance to antimicrobial agents. In conclusion, our experiments uncovered some novel interactions and a synergism between cellular iron levels and drug resistance in Gram‐positive bacteria.